Numerical research on the influence of welding gap on arc morphology in MAG welding of AH36 steel - Shen, Jie; Qi, Dayu; Lai, Rong; Du, Shuoyi (Frontiers in Materials, 2025)
A numerical model of the three-dimensional MAG welding arc for a butt joint with AH36 Steel, incorporating both the welding gap and molten pool structures, was developed. The multi-physical characteristics of the MAG welding arc—including temperature, velocity, and pressure—were analyzed under steady-state conditions for welding gaps ranging from 0 to 2 mm using COMSOL 6.1 software. A detailed comparison of arc morphology under different welding gaps was conducted to explore the mechanism by which variations in the welding gap affect the arc morphology. The results show that the MAG welding arc morphology is basically symmetrically distributed in the direction of the weld cross-section. The arc width and the area of the arc are both consequently larger with increase of welding gap. When the welding current is 150 A and the gap expands from 0 mm to 2 mm, the arc width and area increase by 23.6% and 29.7% respectively. However, in the welding advance direction, the distribution of the arc form is asymmetric due to the presence of a molten pool structure behind the wire. The asymmetry and area of the arc becomes more significant with increase of welding gap. When the welding current is 150 A and the gap increases from 0 mm to 2 mm, the arc area grows by 53.9%, and the arc position drops by 0.29 mm. Finally, the accuracy of the model was validated by a high-speed video camera to capture the arc morphology during welding with varying welding gaps.